Workers' positional power : an input-output relations study - Noguera, Deborah ([Actas])
This paper analyzes the structure of inter-sectoral relations of Argentina's economy, via network analysis tools. The research question focuses on the notion of positionality and how it can explain the power relations between capital and labor. From our point of view, the position held by the different sectors in the economic system reflects the structural advantages of the actors involved in them.